Dispositions of teacher leaders in high impact roles - Lopez, Tonia, author; Sebald, Ann, advisor; Gloeckner, Gene, committee member; Frederiksen, Heidi, committee member; Pendergast, Seth, committee member (Colorado State University. Libraries, 2019)
This study aims to illustrate the dispositions of Teacher Leaders in High Impact Roles. This dissertation is motivated by overarching research questions: What themes emerge from analyzing Grant's Zones and Roles (2008) with Katzenmeyer's dispositions (2009) amongst and between teacher leaders in one school district? A convergent parallel mixed methods study design was used to determine the dispositions of high impact teacher leaders. Qualitative survey questions were coded for the Zones and Roles that teacher leaders were acting in as well as the themes around the dispositions were explored. Quantitative survey questions were examined\ using both descriptive statistics as well as a correlation coefficient to identify if there were any relationships between the Zones and Roles that teacher leaders were in and the dispositions. The study found that teacher leaders demonstrated the dispositions of communication, self-assessment, and instructional knowledge. The research underlined a need to identify how to support teacher leaders who are working closer to classrooms.
Keywords: school change; teacher leadership; school structures; distributed leadership